“Politics of memory”: Interview with Kirsten Emiko McAllister - Premat, Christophe; Sule, Françoise; McAllister, Kirsten Amiko (Sens public)

(untitled) (Département des littératures de langue française, 2010)
For communities who have been the target of political violence, the damaging after-effects can haunt what remains of their families, their communities, and the societies in which they live. This interview with Kirsten Emiko McAllister conducted at the Författarhuset in Stockholm in November 2009 deals with the case of Japanese Canadians in the province of British Columbia. The goal of the interview is to present the work of Kirsten Emiko McAllister: facing painful memories can help to rebuild social and intergenerational links.